Sugar industry in the New Economic Policy in the Left Bank of Ukraine: Historical Context - Olianych, Valentina; Olianych, Larysa (My University, 2022)
The article examines the situation of the sugar industry during the new economic policy in Left-Bank Ukraine. The task is to determine the working conditions of the industry, financing, land issue, and the impact of political events on the development of the sugar industry. The authors identify such important areas of research as recovery, production, achievements, the position of workers during production, the formation of sugar prices, and so on. It is necessary to take into account the conditions of the new economic policy, which significantly changed the life of sugar factories. The article examines the issues of sugar beet cultivation technology and technical support of the industry, the cost and competitiveness of sugar industry products. The article describes the impact of the new conditions on the management of sugar factories in Ukraine as a whole and separately in the Left-Bank Ukraine, as well as the activities of Tsukrotrest. The article examines the importance of the sugar industry for agriculture and for the country’s economy. The authors explore sugar factories in the Left-Bank Ukraine in the article, and also use a vivid example of the Tsyhlerivka Sugar Factory, which is located in the Kharkiv region. This helps to recreate a clear picture of the“ sweet life”, the specifics of the industry. It is concluded that the sugar industry in the NEP environment required a lot of effort to achieve high performance, and indeed, to produce highquality products for the Ukrainian population.
Olianych V. Sugar industry in the New Economic Policy in the Left Bank of Ukraine: Historical Context / Valentina Olianych, Larysa Olianych // Scientific journal of polonia university, 2022. – № 1. – P. 180–185.
Keywords: економічна історія, Українська СРР, сільське господарство, робітники, державне управління; economic history, Ukrainian SSR, agriculture, factory workers, state management